Supporting the Health, Work Ability and Employability of Unemployed People with Long-term Illness - Salminen-Tuomaala, Mari (European Journal of Applied Sciences, 2024)
The article describes a 3-year project called “Duckboards”, carried out in western Finland with long-term unemployed people living with long-term illness. The purpose of the intervention was to test how a multiprofessional team could support the health, work ability and functioning of 145 unemployed clients with long-term illness. Of this group, 45 responded to a quantitative survey, whose purpose was to produce information about how the participants rated the step-by-step intervention and Future Workshop and their encounters with various experts, and to investigate the meaning of the participation for them. Based on the client Likert scale ratings, it would seem that the intervention had a greater positive effect on the participants’ experienced physical and social health and daily coping, compared to job-seeking skills or career planning, where the variance was higher. The participants seemed very satisfied with their encounters and interaction with the project experts.